The unlucky lottery winners of Classroom 13 - Lee, Honest; Gilbert, Matthew J. (Lee, Honest. Classroom 13 series, 2017)
"Unlucky teacher Ms. Linda LaCrosse wins the lottery and shares her winnings with her class. The students fulfill their dreams with their newfound wealth, but they soon learn that winning the lottery is not all that lucky"--